Estudo da apocinina, diapocinina e derivados: síntese, modelagem molecular, avaliação da atividade aceptora de radicais e neuroprotetora frente a sintomas da doença de Parkinson - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Apocynin is phenolic compound with a small structure which exhibit diverse pharmacological activities. Aromatic ring structure can be oxidized under enzymatic or in oxidizing medium generating its dimer, diapocinin. Structural analogues of diapocinin are considering a potential therapeutic agent, and depending on substituent moieties attached to this molecule. Chalcones have a simple chemical 1,3-diaryl-2-propen-1-one structure which allows structural modifications aiming the optimization of the broad recognized pharmacological profile or to reach some different biological activities. Oxygen radical acceptor (antioxidant) and neuroprotective are highlighted biological activities observed to these class of compounds and they were studied in this research. In this work, the synthesis and characterization of diapocinin and its chalcone derivatives, the evaluation of physicochemical properties and radical acceptor activity, molecular modeling and docking studies, in silico and in vivo toxicity, and evaluation of Parkinson’s disease in Drosophila melanogaster protocols were performed in order to support the new antioxidant and antiparkinsonian drugs. Diapocinin was synthesized from apocynin and characterized by HPLC, IR spectroscopy, and 1H and 13C NMR. Chalcones derived from diapocinin, with 4-Cl, 4-N(CH3)2, 4-OCH3 and 4-NO2, were synthesized by the condensation of Claisen-Schmidt. Radical acceptor evaluation was performed usign DPPH assay using BHT as standard. In silico toxicity analysis, specifically the risk of causing genotoxicity, mutagenicity, irritant effects and activity on the reproductive system, were performed using Osiris Property Explorer and admetSAR. Molecular docking studies were performed using iGemdock 2.1 software, and this study involved the evaluation of individual binding of apocynin and diapocinin and alfa-synuclein and NADPH oxidase. In vivo preclinical experimental protocols of activity against Parkinson's disease symptoms were performed with Drosophila melanogaster. Apocynin demonstrated higher DPPH radical capture than diapocynin, suggesting that this compound is the best candidate for the development of compounds with potential antioxidant activity. From the analysis of in silico toxicity, it was observed the 4-N(CH3)2 and 4-NO2 compounds presented risks of causing the mutagenic and genotoxic effects, and the other compounds presented low theoretical risk. The results obtained in the molecular docking study allowed the generation of theoretical models which the apocynin and diapocinin not show binding or interactions in the same molecular protein site. Thus, it is suggested that chemical structures may, simultaneously, act on the same target, but in adjacent sites of interaction. The evaluation of activity against Parkinson's disease symptoms performed by survival, toxicity and behavior assays with Drosophila melanogaster suggest the both apocynin and diapocinin are promising compounds for the study and development of agents to be used in therapy, with neuroprotective activity.
Keywords: Apocinina; Diapocinina; Chalconas; Síntese orgânica; Antioxidante; Antiparkinsoniana; Apocynin; Diapocinin; Chalcone; Organic synthesis; Antioxidant; Antiparkinsonian drugs; Parkinson's disease; Doença de parkinson; Mal de parkinson; CNPQ::CIENCIAS DA SAUDE